2021
DOI: 10.1002/jdd.12624
|View full text |Cite
|
Sign up to set email alerts
|

Reimagining the pipeline: Saturday Academy at New York University College of Dentistry goes virtual

Abstract: Purpose/objectives This study describes and evaluates efforts to transition an established pre‐dental pipeline program to a remote platform, in response to the coronavirus disease 2019 pandemic. Methods The semester‐long pipeline program, Saturday Academy at New York University College of Dentistry, was conducted remotely through Zoom, and materials for hands‐on, pre‐clinical activities, were mailed to participants. Saturday Academy aims to educate underrepresented minority and low‐income high school students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…As diversity programs have been critiqued for their apparent inability to increase the enrollment of dental students of HUREs, we felt that it was important to share outcomes beyond program satisfaction, as previously reported. 27,30 While reports on programmatic outcomes from a single institution may have limited generalizability, we believe that lessons learned from the past 10 years of Saturday Academy at NYU Dentistry can be applied to other dental schools and beyond. This is evidenced by pathway programs at other dental institutions that have been inspired by Saturday Academy at NYU Dentistry.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As diversity programs have been critiqued for their apparent inability to increase the enrollment of dental students of HUREs, we felt that it was important to share outcomes beyond program satisfaction, as previously reported. 27,30 While reports on programmatic outcomes from a single institution may have limited generalizability, we believe that lessons learned from the past 10 years of Saturday Academy at NYU Dentistry can be applied to other dental schools and beyond. This is evidenced by pathway programs at other dental institutions that have been inspired by Saturday Academy at NYU Dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study which included alumni of Saturday Academy at NYU Dentistry found that former participants of pathway programs perceived financial and systemic barriers to their successful application to dental school. 30 Participation in multiple pathway programs helped reduce the negative effects associated with these perceived barriers that students experienced throughout their journeys to dental school. 30 Further, a recent study of US dental school seniors found that for HURE respondents, recruitment activities, inclusive of pathway programs were more likely to be cited as the top reason to get a dental doctoral degree when compared to the overall response group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations